EVALUASI PROGRAM PENGADAAN MERCHANDISE DALAM MEMBANGUN PEMBERDAYAAN EKONOMI PADA KELURAHAN LPDP IPB: Evaluation of the Merchandise Procurement Program in Building Economic Empowerment in the LPDP IPB Subdistrict - azizan, Muhammad (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
This study aims to evaluate the MY LPDP IPB merchandise procurement program in fostering community economic empowerment in the LPDP IPB Village. The program is designed to establish self-funding mechanisms to support the sustainability of community activities, enhance the LPDP's image, and build synergy with local businesses. The research employs a descriptive evaluation approach using the CIPP (Context, Input, Process, and Product) analysis framework, with data collected from activity documentation, interviews, and observations. The findings reveal that the program has successfully generated revenue of Rp 1.6 million through over 170 merchandise orders, forged partnerships with local convection businesses, and strengthened community identity through exclusive products. However, several challenges remain, including suboptimal understanding of consumer preferences, room for improvement in product design quality, and the need for a more integrated promotion and documentation system. The novelty of this study lies in its evaluation approach, which not only focuses on financial outcomes but also considers the broader socio-economic impacts on local partners. The study concludes by emphasizing the importance of developing data-driven strategies, such as consumer preference surveys, enhancing design quality through professional collaboration, and ensuring financial transparency integrated with social media promotions. These initiatives are expected to increase the competitiveness of the MY LPDP IPB program, expand its economic impact, and strengthen the sustainability of the community in the future.